2021
DOI: 10.1080/14787210.2021.1933437
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in SARS-COV2 infection: certainties and uncertainties in clinical practice

Abstract: Introduction The SARS-COV-2 pandemic is a worldwide public health problem due to the large medical burden and limited number of therapies available. Corticosteroids have a rather unclear efficacy in viral non-SARS-COV-2 pneumonias and therefore their use is not universally recommended. In SARS-COV-2 pneumonia however, it is expected that they can reduce the deleterious consequences of the virus-related systemic inflammation. Areas covered a MEDLINE search covering the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…Although some studies have suggested that low-dose corticosteroid therapy appeared to have a beneficial role in managing patients with COVID-19, the results have been controversial. 37 , 38 It is now widely believed that low-dose corticosteroids effectively reduced the risk of mortality, respiratory failure, and delayed viral clearance of patients with severe COVID-19. 13 , 39 , 40 In a study evaluating the effects of low dose of corticosteroids, it was found that, in patients with severe COVID-19, the use of corticosteroids was associated with less likelihood of mortality and care escalation and significantly shorter hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested that low-dose corticosteroid therapy appeared to have a beneficial role in managing patients with COVID-19, the results have been controversial. 37 , 38 It is now widely believed that low-dose corticosteroids effectively reduced the risk of mortality, respiratory failure, and delayed viral clearance of patients with severe COVID-19. 13 , 39 , 40 In a study evaluating the effects of low dose of corticosteroids, it was found that, in patients with severe COVID-19, the use of corticosteroids was associated with less likelihood of mortality and care escalation and significantly shorter hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…For patients treated for COVID-19, one or more of the following were given: clofazimine [20] , ribavirin, interferon beta-1b, or remdesivir [21] . Dexamethasone [22] was added at physicians’ discretion as clinically indicated.…”
Section: Methodsmentioning
confidence: 99%
“…For patients treated for COVID-19, one or more of the following were given: clofazimine (12), ribavirin, interferon beta-1b, or remdesivir (2). Dexamethasone (13) and subcutaneous low-molecular-weight heparin (LMWH) (14) were added at physicians' discretion as clinically indicated. Interferon beta-1b was given once daily subcutaneously at a dose of 16 million IU.…”
Section: Methodsmentioning
confidence: 99%